2021
DOI: 10.1016/j.conengprac.2021.104755
|View full text |Cite
|
Sign up to set email alerts
|

Leakage detection and localization in water distribution systems: A model invalidation approach

Abstract: Model-based methodologies can assist in addressing the challenging problem of leakage detection and localization in water distribution systems. However, this is not trivial due to inherent non-linearities and parametric uncertainties. Most importantly, due to the small number of available sensor measurements compared to the number of system states, the inverse problem for estimating leakages is highly under-determined. In this work, the utilization of a priori available information about the system is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Finally, the clustering depicted in Figure 3b is defined by Equation (17), which is based on the common resistance path explained in Section 3. These two last clusters that only require topological information could be used in the leak localization method at the cluster level defined in Equation (10). It is important to emphasize that the clustering based on the resistance common path, proposed in this paper and depicted in Figure 3b, resembles the clustering based on the actual leak effect in the network (given by the model) depicted in Figure 3c much more than the clustering based in the hydraulic distance depicted in Figure 3a.…”
Section: L1mentioning
confidence: 88%
See 2 more Smart Citations
“…Finally, the clustering depicted in Figure 3b is defined by Equation (17), which is based on the common resistance path explained in Section 3. These two last clusters that only require topological information could be used in the leak localization method at the cluster level defined in Equation (10). It is important to emphasize that the clustering based on the resistance common path, proposed in this paper and depicted in Figure 3b, resembles the clustering based on the actual leak effect in the network (given by the model) depicted in Figure 3c much more than the clustering based in the hydraulic distance depicted in Figure 3a.…”
Section: L1mentioning
confidence: 88%
“…where θ is a normalization factor. Then, θ j can be interpreted as a likelihood index, and the leak localization at cluster level defined in (10) can be formulated at node level as:…”
Section: Leak Localization At Node Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…To consider the uncertainty of model parameters, such as demand uncertainty, sensor noise, and leak sizes, Soldevila et al (2017) reported a method for leak localization based on the Bayesian classifier, which was also tested on the same academic dataset as Ponce et al (2014). More recently, Vrachimis et al (2021) presented leakage detection and localization via model-invalidation, by which the uncertainties of the model parameters including pipe roughness and nodal demand are emulated by the prescribed upper and lower bounds. A 'health' or none-leak condition can be established by the model simulations using the parameters within the bounds.…”
Section: Introductionmentioning
confidence: 99%
“…The role of prior assumptions for leak localisation in water networks with uncertainties 3 with the sensitivities of the pressure measurements to the leak flow from every possible leak location (Casillas et al, 2013). Scenario falsification (Goulet et al, 2013) and model invalidation (Vrachimis et al, 2021) deal with uncertainty by assuming uncertainty bounds, but both methods assume the existence of only a single leak.…”
Section: Introductionmentioning
confidence: 99%